Clinical manifestations and cardiovascular complications of Raynaud’s syndrome - Nojosa Oliveira, Gabriel; Ana Clara Linhares Volpp; Luis Felipe Amaral Bueno; Isabela Machado de Souza; Thaís Augusta Quirino Esteves; Thiago Mendonça Estrela Nascente; Camylla Silva Gomes Paulino; Rejayne Carvalho Branquinho; Luis Felipe Brito Beffart; Juliana Quirino da Silveira; Vinicius Trevisan Alves; Izabella Trevisan Alves (Brazilian Journal of Implantology and Health Sciences, 2024)
Introduction: Raynaud syndrome is a vasomotor disorder that predominantly affects the fingers of the hands and feet, characterized by episodes of pallor, cyanosis and flushing due to changes in blood circulation. These manifestations occur in response to stimuli such as cold or emotional stress, leading to temporary constriction of peripheral blood vessels. Although often benign, the syndrome may be associated with various cardiovascular complications, especially when it occurs in secondary form, related to autoimmune conditions or connective tissue diseases. Understanding clinical manifestations and potential cardiovascular complications is crucial for proper management and more severe impact prevention on patients’ cardiovascular health. Objective: To examine clinical manifestations and cardiovascular complications associated with Raynaud syndrome, analyzing the prevalence, gravity and mechanisms involved in its clinical presentation. METHODOLOGY: For review, checklist prisma was used to ensure transparency and quality of the review. Pubmed, Scielo and Web of Science databases were consulted using five descriptors: “Raynaud syndrome”, “cardiovascular complications”, “clinical manifestations”, “peripheral vasoconstriction” and “autoimmune diseases”. Studies have been included published in the last 10 years. The inclusion criteria were: studies that directly addressed cardiovascular complications of Raynaud syndrome, pairs revised articles and research with original clinical data. The exclusion criteria were: articles outside the established period, case studies not related to cardiovascular complications and articles not available in full text. RESULTS: Review revealed that clinical manifestations of Raynaud syndrome include cyclic changes in extremity coloration and symptoms of pain or discomfort in vasoconstriction phases. Identified cardiovascular complications include pulmonary hypertension and increased risk of peripheral arterial diseases. Studies also indicated an association with autoimmune diseases such as scleroderma, where the severity of symptoms and cardiovascular complications can be accentuated. Conclusion: Raynaud syndrome, in addition to its typical clinical manifestations, is associated with various cardiovascular complications that can significantly impact the patient’s health. Early recognition and proper management of these complications are essential for improving the quality of life and preventing more serious adverse events. Integration of adequate clinical and therapeutic approaches can reduce risk and improve long -term results for affected individuals.